Patterns of Handling Victims of Sexual Violence on Women with Disabilities - Bokiesula Syarifah Yactum Latuconsina; Chazizah Gusnita (Dinasti Publisher, 2024)
Research on the pattern of handling cases of sexual violence against women with disabilities involved several agencies such as National Commission On Violence Against Women, National Commission for Disabilities, HWDI and the PPAPP Office regarding the forms of handling carried out in handling cases of sexual violence. This research uses qualitative methods with data collection techniques through structured interviews with related parties and literature studies. Because of their vulnerability, this research aims to explore patterns of handling sexual violence cases against women with disabilities, focusing on prevention, protection and rehabilitation efforts. The data collected was analyzed using social learning theory in the hope that patterns of handling sexual violence cases can be improved to ensure effective and inclusive protection for all individuals. The results show that the handling of sexual violence cases against women with disabilities still faces various challenges, including lack of awareness, access to services, and discrimination. This research makes an important contribution to understanding the dynamics of handling sexual violence cases against women with disabilities and provides a basis for developing more effective policies and intervention practices to protect their rights.